Evaluation of the oil and gas preservation conditions, source rocks, and hydrocarbon-generating potential of the Qiangtang Basin: New evidence from the scientific drilling project - Li-jun Shen; Jian-yong Zhang; Shao-yun Xiong; Jian Wang; Xiu-gen Fu; Bo Zheng; Zhong-wei Wang (China Geology)
ABSTRACT: The Qiangtang Basin of the Tibetan Plateau, located in the eastern Tethys tectonic domain, is the largest new marine petroliferous region for exploration in China. The scientific drilling project consisting primarily of well QK-1 and its supporting shallow boreholes for geological surveys (also referred to as the Project) completed in recent years contributes to a series of new discoveries and insights into the oil and gas preservation conditions and source rock evaluation of the Qiangtang Basin. These findings differ from previous views that the Qiangtang Basin has poor oil and gas preservation conditions and lacks high-quality source rocks. As revealed by well QK-1 and its supporting shallow boreholes in the Project, the Qiangtang Basin hosts two sets of high-quality regional seals, namely an anhydrite layer in the Quemo Co Formation and the gypsum-bearing mudstones in the Xiali Formation. Moreover, the Qiangtang Basin has favorable oil and gas preservation conditions, as verified by the comprehensive study of the sealing capacity of seals, basin structure, tectonic uplift, magmatic activity, and groundwater motion. Furthermore, the shallow boreholes have also revealed that the Qiangtang Basin has high-quality hydrocarbon source rocks in the Upper Triassic Bagong Formation, which are thick and widely distributed according to the geological and geophysical data. In addition, the petroleum geological conditions, such as the type, abundance, and thermal evolution of organic matter, indicate that the Qiangtang Basin has great hydrocarbon-generating potential.©2023 China Geology Editorial Office.